Counter-Terrorism Laws: Analysis of Selected International and Regional Frameworks - Attah, Christiana Ejura (Kashere Journal of Politics and International Relations, 2025)
Robust legal frameworks are essential in the global struggle against terrorism, as they facilitate international cooperation, protect human rights, and enhance security. This article analyses the counterterrorism legislative frameworks established by four key international organisations: the United Nations (UN), the Organization of African Unity (OAU)/African Union (AU), the European Union (EU), and the Organisation of American States (OAS). It discusses the development and importance of these frameworks, emphasising their definitions of terrorism, strategies for addressing terrorism financing, and measures to uphold human rights. The paper reviews the significant legal documents ratified by each organisation, including OAS treaties, AU conventions, EU directives, and UN Security Council resolutions. Furthermore, it explores the relationships between these frameworks and their impact on national counterterrorism laws within member states. Despite their strengths, these frameworks encounter challenges such as jurisdictional disputes, enforcement limitations, and the evolving nature of terrorist threats. The study concludes that successful counter-terrorism efforts depend on strengthened multilateral cooperation and compliance with international legal standards.